Experiences of bereaved family caregivers of patients with CTCL. (1st October 2018) - Orlowska, D.; Selman, L.E.; Beynon, T.; Radcliffe, E.; Whittaker, S.; Child, F.; Harding, R.
Summary: Cutaneous T‐cell lymphomas (CTCL) are rare types of skin cancer. Skin may develop tumours or ulcers. Sometimes these may cover quite large areas and feel itchy or uncomfortable. Internal body parts may be affected in more advanced disease. Only a few people are diagnosed each year (8 per million), so most GPs do not meet people with this disease. This study from the U.K. aimed to find out about the experiences of family or close friends of people who had died because of the disease (not all people with this disease die of it). Relatives of 11 patients with CTCL who had died were interviewed, four months or more after the death. The themes from what they said are described. Family members gave vivid descriptions of how the illness changed the appearance of their relative. They spoke of how difficult it was to look after someone with very damaged skin. They described the many different things they had to do to care for their relative both in hospital and at home. Some patients had frequently been in and out of hospital. Some caregivers expected them to come home each time and so had not felt prepared when their relative died. Several caregivers described how upsetting it was to see how illness affected their relative before they died. The authors say that family caregivers should be seen as part of the care team looking after the patient. They recommend that carers' needs for practical and emotional support and information should be considered during each patient's illness. Support for carers should also be offered following the death of their relative.